2015
DOI: 10.1371/journal.pone.0144946
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ursolic Acid on Leishmania (Leishmania) amazonensis Is Related to Programed Cell Death and Presents Therapeutic Potential in Experimental Cutaneous Leishmaniasis

Abstract: Among neglected tropical diseases, leishmaniasis is one of the most important ones, affecting more than 12 million people worldwide. The available treatments are not well tolerated, and present diverse side effects, justifying the search for new therapeutic compounds. In the present study, the activity of ursolic acid (UA) and oleanolic acid (OA) were assayed in experimental cutaneous leishmaniasis (in vitro and in vivo). Promastigote forms of L. amazonensis were incubated with OA and UA for 24h, and effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 61 publications
(63 reference statements)
2
58
0
7
Order By: Relevance
“…Furthermore, UA was confirmed to possess antiprotozoal activities. Similarly to its effect on tumor cells, this triterpene induced programmed cell death in L. (L.) amazonensis , and presented therapeutic efficacy in the model of American Tegumentar Leishmaniasis (Yamamoto et al., 2015). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, UA was confirmed to possess antiprotozoal activities. Similarly to its effect on tumor cells, this triterpene induced programmed cell death in L. (L.) amazonensis , and presented therapeutic efficacy in the model of American Tegumentar Leishmaniasis (Yamamoto et al., 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Although the leishmanicidal action of UA ( in vitro ) was already evaluated (Passero et al., 2011, Yamamoto et al., 2015), its action in experimental models of leishmaniasis was poorly demonstrated until now. In this regard, Yamamoto and collaborators (Yamamoto et al., 2014) showed that UA treatment of L. (L.) amazonensis- infected BALB/c mice decreased skin parasitism, which was associated with the preservation of the epidermis and dermis as a possible consequence of IFN-γ production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitric oxide (NO) production by host macrophages has been considering one of the key weapons used for the antimicrobial defense against intracellular pathogens, including Leishmania parasites . Many plant‐derived compounds have been described to increase NO production in macrophage as a Leishmania killing mechanism . Therefore, the present work suggests that tricin ( 1 ) modulated the respiratory burst of macrophage to a leishmanicidal state, possibly contributing to the parasite elimination.…”
Section: Resultsmentioning
confidence: 89%
“…Moreover, these PCTs might be involved in maintaining the mechanical strength of the cuticular matrix by functioning as nanofillers (Tsubaki et al, 2013). Ursolic acid and oleanolic acid exhibit a wide spectrum of pharmacological activities, including anti-carcinogenic, hepatoprotective, antiinflammatory, anti-oxidant and anti-microbial properties, and products based on these PCTs are available in global markets as dietary supplements, over-the-counter drugs and cosmetics (Kunkel et al, 2011;Pollier & Goossens, 2012;Wo zniak et al, 2015;Yamamoto et al, 2015;Kashyap et al, 2016;Silva et al, 2016). Moreover, oleanolic acid derivatives (bardoxolone methyl and omaveloxolone) are currently undergoing advanced clinical studies for the treatment of pulmonary hypertension, chronic kidney disease, Friedreich's ataxia, mitochondrial myopathies and melanoma patients, and for the prevention of corneal endothelial cell loss in cataract surgery patients (http://reatapharma.com/).…”
Section: Introductionmentioning
confidence: 99%